LO04: Decreasing emergency department length of stay for patients with acute atrial fibrillation and flutter: a cluster-randomized trial. (May 2020) - Stiell, I.; Eagles, D.; Perry, J.; Archambault, P.; Thiruganasambandamoorthy, V.; Parkash, R.; Mercier, E.; Morris, J.; Godin, D.; Davis, P.; Clark, G.; Gosselin, S.; et al.
Abstract : Introduction: CAEP recently developed the acute atrial fibrillation (AF) and flutter (AFL) [AAFF] Best Practices Checklist to promote optimal care and guidance on cardioversion and rapid discharge of patients with AAFF. We sought to assess the impact of implementing the Checklist into large Canadian EDs. Methods: We conducted a pragmatic stepped-wedge cluster randomized trial in 11 large Canadian ED sites in five provinces, over 14 months. All hospitals started in the control period (usual care), and then crossed over to the intervention period in random sequence, one hospital per month. We enrolled consecutive, stable patients presenting with AAFF, where symptoms required ED management. Our intervention was informed by qualitative stakeholder interviews to identify perceived barriers and enablers for rapid discharge of AAFF patients. The many interventions included local champions, presentation of the Checklist to physicians in group sessions, an online training module, a smartphone app, and targeted audit and feedback. The primary outcome was length of stay in ED in minutes from time of arrival to time of disposition, and this was analyzed at the individual patient-level using linear mixed effects regression accounting for the stepped-wedge design. We estimated a sample size of 800 patients. Results: We enrolled 844 patients with none lost to follow-up. Those in the control (N = 316) and intervention periods (N = 528) were similar for all characteristics including mean age (61.2 vs 64.2 yrs), duration of AAFF (8.1 vs 7.7 hrs), AF (88.6% vs 82.9%), AFL (11.4% vs 17.1%), and mean initial heart rate (119.6 vs 119.9 bpm). Median lengths of stay for the control and intervention periods respectively were 413.0 vs. 354.0 minutes (P < 0.001). Comparing control to intervention, there was an increase in: use of antiarrhythmic drugs (37.4% vs 47.4%; P < 0.01), electrical cardioversion (45.1% vs 56.8%; P < 0.01), and discharge in sinus rhythm (75.3% vs. 86.7%; P < 0.001). There was a decrease in ED consultations to cardiology and medicine (49.7% vs 41.1%; P < 0.01), but a small but insignificant increase in anticoagulant prescriptions (39.6% vs 46.5%; P = 0.21). Conclusion: This multicenter implementation of the CAEP Best Practices Checklist led to a significant decrease in ED length of stay along with more ED cardioversions, fewer ED consultations, and more discharges in sinus rhythm. Widespread and rigorous adoption of the CAEP Checklist should lead to improved care of AAFF patients in all Canadian EDs.